THE ROLE OF PURCHASE INTENTION ON INTERNATIONAL FOOD BRANDS DURING COVID-19 PANDEMIC - Sant Louis Liewin; Genoveva Genoveva (President University, 2021)
The corona virus has attacked human life by taking away their freedom. Since the spread of the corona virus throughout the world at the end of 2019, every country has issued social distancing policies, including in Indonesia. The impact of this viral pandemic has damaged various existing businesses, including food franchises with international brands. The purpose of thisstudy isto analyze purchasing decisions at fast food franchises with international brands, assuming international brands already have cleanliness standards, high quality and a more comfortable environment (location), so that consumer confidence is more than other local brands. The trust factor is also used in this study as an intervening variable. This research is a quantitative study using an online questionnaire as a data collection tool. The valid questionnaires are filled in by 180 respondents. The sample used was non-purposived sampling with simple random sampling. Hypothesis testing uses the Structural Equation Model (SEM). The results showed that Food Safety, Food Quality and Environment had a significant effect on Purchasing Decisions during the COVID-19 pandemic. Meanwhile, Quality and Environment have a significant effect on trust, which is an intervening variable in this study. This study concludes that Food Safety, Food Quality, and Environment have a positive and significant effect on consumer confidence so that it affects purchasing decisions. Keywords: Franchise, fast food, Covid-19, pandemic, trust, purchase decision.